Initiating Care of a Patient With Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) - Lapp, Charles W. (Frontiers in Pediatrics, 2019)
This paper introduces the primary care physician to the unique and challenging aspects of initially diagnosing and managing a complex condition for which there a plethora of symptoms, few physical findings, no known cause, and no specific treatments. While daunting, the rewards are many, and those who pursue an interest in ME/CFS find themselves at the forefront of medicine.